Numerical simulation of natural ventilation for full-scale office in Malaysia - Wahhad, Ali M.; M. Elfaghi, Abdulhafid (Journal of Scientific & Technology Research, 2018)
The Natural ventilation is the sustainable solution to maintain the health and environmental conditions comfortable in buildings. This paper presents a 3D computational fluid dynamics (CFD) analysis to investigate indoor environmental conditions of naturally ventilated typical size of single office room of a high-glass wall fitted with two operable windows. The purpose of this work is to facilitate design and analysis of suitable window measurements. The numerical results obtained for a particular time (solar time) available and the maximum discrepancy obtained are 1.7% of temperature and 3% of velocity which are within the accepted level and computations with the CFD based model show best agreement with measurements and good thermal comfort is achieved when the outdoor temperature is moderate.